Comparative Map History and "the History of Cartography" : Methodologies, Institutions, and Idealizations - Edney, Matthew H., (Brill Research Perspectives in Humanities and Social Sciences ;, 2025)
The apparently centuries-old field of "the history of cartography" was invented after 1950 through incomplete historiographies by leading map historians. This monograph uses an empirically grounded analysis of the ways in which early maps have been systematically studied since the early 1800s to offer an innovative account of the practices and institutions of comparative map history in support of Western imperialism and nationalism, and of how the field was reconfigured as the core of a newly idealized discipline of "the history of cartography."